Hydroxytyrosol protects isoproterenol-induced myocardial infarction through activating notch signaling - Onat, Elif; Turk, Ahmet; Kocaman, Nevin; Hancer, Serhat; Susam, Solmaz; Parlar, Ali; Ozer, Mehmet Kaya (Mashhad Univ Med Sciences, 2025)
Objective(s): In this investigation, the protective effects of hydroxytyrosol (HT) administered prior to myocardial infarction in rats were examined, with a particular focus on its potential roles within the Notch pathway. Materials and Methods: The animals were categorized into seven groups (n=7): control, myocardial infarction (MI) 6 (th) hr, MI 24(th) hr, MI 7( th) day, MI+HT 6 (th )hr, MI+HT 24(th) hr, MI+HT 7 (th) day. In order to create infarction, the rats received a subcutaneous injection of isoproterenol at a dose of 200 mg/kg. Rats were given 4 ml/kg/day liquid containing HT orally for six weeks before infarction. Histopathological examination was conducted on heart tissue to assess Notch1, Hes1, and DLL4. Biochemical parameters were analyzed in serum using the ELISA method. Results: The study revealed an increase in Notch1 and DLL4 levels, particularly at the 24(th) hr and 7( th )day after the occurrence of myocardial infarction. DLL4 increased at 24 hr and 7 days of infarction after HT administration compared to control. Hes1 levels increased towards the seventh day after infarction and following HT application before infarction. It was noted that the severity of histopathological damage in heart tissue was reduced at the 24(th) hr of infarction in rats treated with HT prior to infarction. A significant decrease in fibrosis was observed on the seventh day of infarction in rats given HT before infarction. The levels of biochemical parameters decreased with the administration of HT before the occurrence of infarction. Conclusion: HT is thought to exert a cardioprotective effect in MI, potentially mediated through the Notch pathway.
Keywords: DLL4; Hes1; Hydroxytyrosol; Myocardial infarction; Notch1